-5k-4(k-3)=-6k+3

Simple and best practice solution for -5k-4(k-3)=-6k+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5k-4(k-3)=-6k+3 equation:


Simplifying
-5k + -4(k + -3) = -6k + 3

Reorder the terms:
-5k + -4(-3 + k) = -6k + 3
-5k + (-3 * -4 + k * -4) = -6k + 3
-5k + (12 + -4k) = -6k + 3

Reorder the terms:
12 + -5k + -4k = -6k + 3

Combine like terms: -5k + -4k = -9k
12 + -9k = -6k + 3

Reorder the terms:
12 + -9k = 3 + -6k

Solving
12 + -9k = 3 + -6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '6k' to each side of the equation.
12 + -9k + 6k = 3 + -6k + 6k

Combine like terms: -9k + 6k = -3k
12 + -3k = 3 + -6k + 6k

Combine like terms: -6k + 6k = 0
12 + -3k = 3 + 0
12 + -3k = 3

Add '-12' to each side of the equation.
12 + -12 + -3k = 3 + -12

Combine like terms: 12 + -12 = 0
0 + -3k = 3 + -12
-3k = 3 + -12

Combine like terms: 3 + -12 = -9
-3k = -9

Divide each side by '-3'.
k = 3

Simplifying
k = 3

See similar equations:

| 5(x+2)-3=2x+3(1+x) | | 40*x=X-100 | | 6m^2+2m-17=0 | | (2x+6)+(x+9)=90 | | 2x-3y(x-1)=-1 | | -k+35=-7(-5-8k) | | 107+2x-5=180 | | 2(2+3y)+3y=15 | | x+2x-5=107 | | 9x^2-70+49=0 | | 2x+-3y(6x-11)=-7 | | (6x^2)-30x=0 | | (6x^2)-30y=0 | | (6x+48)=(12x+24) | | 26.2=9t | | 3b-3-4b=2 | | 10=1+r+5 | | y=4+0.01x | | x^4-2x^2-6x+3=0 | | 3z+6=5z-4 | | 26+3n=-2(n+2)-n | | X^3+13=6x | | 23=2u-11 | | (8x-20)+(3x+15)=88 | | 36=5(w+3)-8w | | 3a+a=4*2 | | 2x+48=9x+13 | | y=10-0.01x | | 5x-2-3x=3x-3-8 | | 7b-15=5b-s | | 5a+3b-c= | | 289= |

Equations solver categories